An assessment of supplier development in the Zimbabwean cotton industry - Paul Mukucha; Felix Chari (Cogent Business & Management, 2024)
Supplier development in the form of contract farming has become the main sourcing strategy in agro-processing industry. However, it is not yet clear from the extant literature how investments in contract farming contribute towards yield per yield. More specifically, this study sought to determine the effects of supplier development in contract farming investments on cotton yield in kilograms per hectare. It furthermore, seeks to unravel whether contract farming initiatives lead to the yield that exceeds 2000 kg/hectare as specified by the Zimbabwe regulatory authority's target. The study uses secondary data obtained on average national cotton contact farming investments per hectare in monetary terms. The output yield per hectare is obtainable from several publications by the Agricultural Marketing Authority (AMA). The statistics cover the period between year 2011 and 2016. Statistical data analysis of the study is accessed through the Statistical Package for Social Scientists (SPSS) using simple linear regression for the first hypothesis, and One-sample t-test for the second hypothesis. Supplier development initiatives' impact on yield is found to be statistically significant indicating that for every one unit increase in dollar investments yield changes by 1.161 kg of harvested cotton seed. The results also show that the mean cotton yield in kg/hectare is by far below the national set target of two thousand (2000) kg/hactare. The study recommends that the levels of investments ought to be increased in order to impact positively on yield in order to attain the desired yield per hectare.
Keywords: 650; Contact farming; procurement; sourcing; supplier development